Redirecting T-Cell Specificity to EGFR Using mRNA to Self-limit Expression of Chimeric Antigen Receptor. Issue 5 (June 2016) - Caruso, Hillary G.; Torikai, Hiroki; Zhang, Ling; Maiti, Sourindra; Dai, Jianliang; Do, Kim-Anh; Singh, Harjeet; Huls, Helen; Lee, Dean A.; Champlin, Richard E.; Heimberger, Amy B.; Cooper, Laurence J.N.
Abstract : Potential for on-target, but off-tissue toxicity limits therapeutic application of genetically modified T cells constitutively expressing chimeric antigen receptors (CARs) from tumor-associated antigens expressed in normal tissue, such as epidermal growth factor receptor (EGFR). Curtailing expression of CAR through modification of T cells by in vitro-transcribed mRNA species is one strategy to mitigate such toxicity. We evaluated expression of an EGFR-specific CAR coded from introduced mRNA in human T cells numerically expanded ex vivo to clinically significant numbers through coculture with activating and propagating cells (AaPC) derived from K562 preloaded with anti-CD3 antibody. The density of AaPC could be adjusted to affect phenotype of T cells such that reduced ratio of AaPC resulted in higher proportion of CD8 + and central memory T cells that were more conducive to electrotransfer of mRNA than T cells expanded with high ratios of AaPC. RNA-modified CAR + T cells produced less cytokine, but demonstrated similar cytolytic capacity as DNA-modified CAR + T cells in response to EGFR-expressing glioblastoma cells. Expression of CAR by mRNA transfer was transient and accelerated by stimulation with cytokine and antigen. Loss of CAR abrogated T-cell function in response to tumor and normal cells expressing EGFR. We describe a clinically applicable method to propagate and modify T cells to transiently express EGFR-specific CAR to target EGFR-expressing tumor cells that may be used to limit on-target, off-tissue toxicity to normal tissue. Abstract : Supplemental Digital Content is available in the text.